Red Blood Cell Transcriptome Reflects Physiological Responses to Alternative Nutrient Sources in Gilthead Seabream (Sparus aurata) - Rafael Angelakopoulos; Andreas Tsipourlianos; Alexia E. Fytsili; Leonidas Papaharisis; Arkadios Dimitroglou; Dimitrios Barkas; Zissis Mamuris; Themistoklis Giannoulis; Katerina A. Moutou (Animals)
The sustainable growth of finfish farming relies heavily on reducing the high ecological footprint of sourcing and producing fish feeds that accounts for almost 50% of the total ecological footprint of finfish farming. Sustainable alternatives to fishmeal often pose challenges due to the presence of antinutritional factors and nutrient imbalances that impair fish health and growth. Screening for alternative nutrient sources and adapting to global commodity fluctuations requires modern tools that can predict the physiological responses of fish early and reliably. The present study explores for the first time the potential of fish red blood cell (RBC) transcriptome as a minimally invasive biomarker of physiological responses in gilthead seabream (Sparus aurata) fed either a fishmeal-based (FM) or a plant-protein-based (PP) diet. Blood samples were collected at multiple time points (15, 20, and 30 days post-diet initiation) from genetically diverse full-sib families reared under commercial conditions, integrating transcriptomic analysis with long-term growth assessments. Differential gene expression analysis revealed significant dietary effects on oxidative phosphorylation, ribosomal capacity, and lipid metabolism pathways, highlighting metabolic plasticity and cellular adaptations to plant-based feeds. The downregulation of oxidative phosphorylation genes suggests a metabolic shift in response to altered nutrient composition, while ribosomal pathway modulation indicates potential constraints on protein synthesis. These transcriptomic shifts, conserved across two independent experiments, reinforce the utility of RBCs as a real-time indicator of fish physiological status, offering a tool for monitoring dietary impacts and optimizing feed formulations. Such insights are essential for advancing sustainable, nutritionally balanced aquaculture feeds that support fish welfare and productivity. The minimally invasive sample collection respects the 3Rs (Reduce, Refine, Replace) principle in animal experimentation and allows for frequent screening and generation of refined data.